The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0126581
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Stress during Stand Development Alters the Sign and Magnitude of Age-Related Growth Responses in a Subtropical Mountain Pine

Abstract: The modification of typical age-related growth by environmental changes is poorly understood, In part because there is a lack of consensus at individual tree level regarding age-dependent growth responses to climate warming as stands develop. To increase our current understanding about how multiple drivers of environmental change can modify growth responses as trees age we used tree ring data of a mountain subtropical pine species along an altitudinal gradient covering more than 2,200 m of altitude. We applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Overall, the importance of the interaction between climate and forest development agrees with previous studies that identified similar strong interactions for tree growth (e.g. Gómez‐Aparicio, García‐Valdés, Ruiz‐Benito, & Zavala, ; Ruiz‐Benito et al., ), tree mortality (e.g. Ruiz‐Benito et al., ; Vilà‐Cabrera, Martínez‐Vilalta, Vayreda, & Retana, ), recruitment (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, the importance of the interaction between climate and forest development agrees with previous studies that identified similar strong interactions for tree growth (e.g. Gómez‐Aparicio, García‐Valdés, Ruiz‐Benito, & Zavala, ; Ruiz‐Benito et al., ), tree mortality (e.g. Ruiz‐Benito et al., ; Vilà‐Cabrera, Martínez‐Vilalta, Vayreda, & Retana, ), recruitment (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…in northeast Hamburg of northern Germany, Pinus taiwanensis Hayata. in Taiwan, and Pinus cooperi Blanco in the Sierra Madre Occidental of northern Mexico [57][58][59][60]. As shown by a controlled experiment on cambial cell sensitivity to rising temperature of Cryptomeria japonica (L. f.) D. Don from different ages, the young tree growth trend would more easily be limited by long-term drought [61].…”
Section: Age-effect On Tree Radial Growthmentioning
confidence: 99%
“…To date, comparative studies have investigated on phenology patterns of young and mature growth as well as the environmental sensitivities (Esper et al, ; Li et al, ; Ruiz‐Benito et al, ). Compared to adult trees of deciduous species, seeding and saplings have been found to be characterized by an earlier flushing, an earlier xylem formation, a longer growth season and a growth rate (Augspurger & Bartlett, ; Li et al, ; Vitasse, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this trajectory can be complex, because tree performance in response to climate warming may be mediated by traits related to resource acquisition (Chen, An, Inouye, & Schwartz, 2015;Dorji et al, 2013;Estiarte & Peñuelas, 2015;Schwartz, Hanes, & Liang, 2014), such as life-history phases (juvenile vs. mature forest). However, variability in phenological plasticity and sensitivity to elevated temperature over the plant life cycle is not well known; we lack the insight on how age structure affects tree growth in the future warmer world (Esper, Niederer, Bebi, & Frank, 2008;Ruiz-Benito et al, 2015;Xu, Yin, Xiong, Wan, & Liu, 2012).…”
mentioning
confidence: 99%